2019
DOI: 10.31539/jks.v3i1.841
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penyuluhan Identifikasi dengan Menggunakan Media Audiovisual terhadap Pengetahuan Pasien Rawat Inap

Abstract: The purpose of this study was to determine the effect of audiovisual media application of patient identification implementation on patient knowledge at the University of North Sumatra Hospital in 2019. The study used a quantitative approach, with quasi-experimental methods, one group pre-test-post-test design. The results showed that before counseling, 40 patients included in the category of sufficient knowledge, and 80 people in the category of insufficient knowledge. After counseling using audiovisual media,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
17

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 0 publications
0
10
0
17
Order By: Relevance
“…The results of the characteristics of the correspondent showed that the majority of ages between 25 to 30 years, this is an age that is still productive and has good performance so that it has the potential to work better (Harina, 2003).In one study it was said that ages 30-39 were mature and had good thinking and a good grasp of science (Simamora, 2019). In the world of nursing so far the most are women, this is because nurses are identical to the role of the mother or woman (mother instinct) who treats with better work results (Harina, 2003), but the results in Table 1 show compliance with identification made possible by men this happens because of a lack of sampling.…”
Section: Lack Of Supervision 6 Materialsmentioning
confidence: 99%
“…The results of the characteristics of the correspondent showed that the majority of ages between 25 to 30 years, this is an age that is still productive and has good performance so that it has the potential to work better (Harina, 2003).In one study it was said that ages 30-39 were mature and had good thinking and a good grasp of science (Simamora, 2019). In the world of nursing so far the most are women, this is because nurses are identical to the role of the mother or woman (mother instinct) who treats with better work results (Harina, 2003), but the results in Table 1 show compliance with identification made possible by men this happens because of a lack of sampling.…”
Section: Lack Of Supervision 6 Materialsmentioning
confidence: 99%
“…Regular in-service education should be provided to all medical and non-medical personnel in the health care environment. In addition, pre-service education for all health workers should also address standard precautions [14,15].…”
Section: Characteristics Ofmentioning
confidence: 99%
“…The government can use simple technology in carrying out extension activities by using audio and visual media (Simamora, 20119). Local governments create specific YouTube channels that their extension workers prepare and are expected to develop content related to agriculture.…”
Section: The Ability Of Farmers To Read and Writementioning
confidence: 99%